2011
DOI: 10.1084/jem.2010189020813c
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclasts are dispensable for hematopoietic stem cell maintenance and mobilization

Abstract: The authors regret that the dosage of RANKL and control antibodies used in the HSC mobilization experiments shown in Figure 6 were incorrectly reported in micrograms. The correct dosages were 5 mg/kg anti-RANKL and 2.5 mg/kg control antibody. The html and pdf versions of the article have been corrected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 0 publications
2
57
0
Order By: Relevance
“…This suggests that spleen acts as the reservoir of hematopoietic precursors under pathological conditions such as osteopetrosis. Recently, Miyamoto et al (36) reported that the mobilization of hematopoietic stem and progenitor cells (HSPCs) occurring after granulocyte colony-stimulating factor (G-CSF) injection was comparable or even increased in osteopetrotic CSF-1 op/op , RANKL −/− and c-Fos −/− mice, compared with that in WT mice. Contrary to OCPs, the mobilization of HSPCs was not suppressed by SPX in CSF-1 op/op mice in the G-CSF treatment (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that spleen acts as the reservoir of hematopoietic precursors under pathological conditions such as osteopetrosis. Recently, Miyamoto et al (36) reported that the mobilization of hematopoietic stem and progenitor cells (HSPCs) occurring after granulocyte colony-stimulating factor (G-CSF) injection was comparable or even increased in osteopetrotic CSF-1 op/op , RANKL −/− and c-Fos −/− mice, compared with that in WT mice. Contrary to OCPs, the mobilization of HSPCs was not suppressed by SPX in CSF-1 op/op mice in the G-CSF treatment (36).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Miyamoto et al (36) reported that the mobilization of hematopoietic stem and progenitor cells (HSPCs) occurring after granulocyte colony-stimulating factor (G-CSF) injection was comparable or even increased in osteopetrotic CSF-1 op/op , RANKL −/− and c-Fos −/− mice, compared with that in WT mice. Contrary to OCPs, the mobilization of HSPCs was not suppressed by SPX in CSF-1 op/op mice in the G-CSF treatment (36). These results suggest that spleen cannot act as the reservoir of HSPCs in CSF-1 op/op mice, although HSPCs exist in the enlarged spleen.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that active osteoclasts are indispensable for endosteal HSC/ HPC niche formation. Another group reported that osteopetrotic mice models, op/op, c-Fos-deficient, and receptor activator of nuclear factor kappa B ligand-deficient mice, in which osteoclasts are deficient and BM cavity is absent, have normal capacity for HSC/HPC mobilization induced by granulocyte colony-stimulating factor (G-CSF) [27]. Therefore, the role of osteoclasts in hematopoietic system remains a matter of debate.…”
Section: Osteoblast Progenitor (Pre-osteoblast) and Osteoblastmentioning
confidence: 99%
“…Macrophage depletion strategies using clodronate liposome and the macrophage-Fas-induced apoptosis (Mafia) models both reduced osteoclast numbers, yet resulted in robust HSC mobilization [28]. Administration of bisphosphonates and anti-RANKL antibody to suppress OC activity instead enhanced mobilization of HSPCs in response to G-CSF [28,29,44]. Furthermore, the timing of G-CSF-induced elevation in osteoclast number and activity seems to occur after the peak of HSPC mobilization [28,29].…”
Section: Osteoclastsmentioning
confidence: 99%
“…Furthermore, the timing of G-CSF-induced elevation in osteoclast number and activity seems to occur after the peak of HSPC mobilization [28,29]. Studies utilising gene knockout models with defective OCs at birth are confounded by a perturbed BM niche, including osteopetrosis, leading to abnormal levels and response of HSPCs depending on the severity of the OC defect [44,45]. A recent study by Daniel Link's group employing two mouse models with selective OC depletion without osteopetrosis again found no effect on G-CSF-induced HSPC mobilization [46].…”
Section: Osteoclastsmentioning
confidence: 99%